Negative electrode active material, negative electrode containing the negative electrode active material, secondary battery containing the negative electrode, and method for preparing the negative electrode active material

By using metal-silicon-carbon particles containing MaSibC matrix in the negative electrode active material of the secondary battery, the problem of irreversible phase formation of silicon particles such as SiOx (0≤x<2) during the charging and discharging process is solved, and the initial efficiency, capacity and life of the battery are significantly improved.

CN112272876BActive Publication Date: 2025-03-14LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980039724.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-19
Filing Date
2019-10-18
Publication Date
2025-03-14
Estimated Expiration
2040-01-16

AI Technical Summary

Technical Problem

Silicon particles such as SiOx (0≤x<2) used in existing secondary batteries have irreversible phases formed during charging and discharging, resulting in low initial efficiency, reduced capacity and life, and difficult to effectively control.

Method used

Metal-silicon-carbon particles containing MaSibC matrix are used as the negative electrode active material. By doping metal into the SiCx matrix, excellent conductivity, mechanical strength and chemical stability are formed, thereby reducing the formation of irreversible phases.

Benefits of technology

By using the negative electrode active material of the MaSibC matrix, the initial efficiency, capacity and life characteristics of the secondary battery are significantly improved, and the formation of irreversible phases is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002833482410000171
    Figure BDA0002833482410000171
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material, comprising M a Si b C-based metal-silicon-carbon particles, wherein the M a Si b M in the C matrix is ​​at least one selected from the group consisting of Li, Mg, Na, Ca and Al, 0.3≤a≤1 and 1≤b≤2. a Si b C matrix, the formation of irreversible phases during charge and discharge of the battery can be minimized, so that the initial efficiency of the battery can be improved, and the capacity and life characteristics of the battery can be improved due to improved conductivity, physical strength and chemical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0124980, filed on October 19, 2018, which is hereby incorporated by reference in its entirety. Technical Field

[0004] The present disclosure relates to a negative electrode active material, a negative electrode comprising the negative electrode active material, a secondary battery comprising the negative electrode, and a method for preparing the negative electrode active material, and more particularly, to a negative electrode comprising SiC x A negative electrode active material of the matrix; and a x Metallic silicon-carbon based particles on a substrate. Background Art

[0005] Due to the rapid increase in the use of fossil fuels, the demand for the use of alternative or clean energy has increased. As a part of this, the most active research field is the field of power generation and storage using electrochemical reactions.

[0006] At present, the representative example of the electrochemical device using electrochemical energy as described above is a secondary battery, and the use field of the secondary battery is gradually increasing. At present, with the increase in the technical development and demand for portable devices such as portable computers, portable phones, cameras, etc., the demand for secondary batteries as energy sources is also rapidly increasing. Among these secondary batteries, lithium secondary batteries with high energy density, i.e., high-capacity lithium secondary batteries, have been widely studied and commercialized, and thus are widely used.

[0007] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material that allows lithium ions from the positive electrode to be intercalated and deintercalated, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used. However, SiO x When the secondary battery is charged, SiO2 of silicon-based particles such as (0≤x<2) reacts with Li ions generated from the positive electrode to form lithium silicate as an irreversible phase. Therefore, the initial efficiency of the battery is low. In addition, due to the x Silicon-based particles such as (0≤x<2) have an excessively large volume change during the charge and discharge process and have low conductivity, thus causing a problem of reduced battery life.

[0008] In the related art, in order to solve these problems, a technology of forming a coating on the surface of silicon-based particles has been used. In detail, there is a method of forming a carbon coating on the surface of silicon-based particles (Korean Patent Gazette 10-2015-0112746). However, even in the case of forming a carbon coating, it is difficult to control the formation of an irreversible phase, and the effect of reducing battery resistance is not great.

[0009] Therefore, a method is needed to replace SiO x (0≤x<2) while improving the initial efficiency, capacity and life characteristics of the battery.

[0010] [Related technical literature]

[0011] [Patent document]

[0012] Korean Patent Gazette 10-2015-0112746 Summary of the invention

[0013]

Technical issues

[0014] One aspect of the present disclosure provides a negative electrode active material that can suppress an irreversible reaction in a battery reaction to improve initial efficiency, and can improve capacity and life characteristics of a battery due to its excellent conductivity, mechanical strength, and chemical stability.

[0015] Another aspect of the present disclosure provides a method for preparing the negative electrode active material.

[0016] Another aspect of the present disclosure provides a negative electrode including the negative electrode active material and a secondary battery including the negative electrode.

[0017]

Technical solution

[0018] According to an exemplary embodiment of the present disclosure, there is provided a negative electrode active material comprising M a Si b C-based metal-silicon-carbon particles, wherein the M a Si b M in the C matrix is ​​one or more selected from the group consisting of Li, Mg, Na, Ca and Al, 0.3≤a≤1 and 1≤b≤2.

[0019] According to another exemplary embodiment of the present disclosure, a method for preparing the above-mentioned negative electrode active material is provided, comprising introducing a vaporized silicon source, a carbon source, a metal source and a carrier gas into a reaction furnace, and forming a matrix fluid through heat treatment, wherein in the formation of the matrix fluid, the ratio of the flow rate of the vaporized silicon source, the flow rate of the carbon source and the flow rate of the metal source is 1:0.2:0.2 to 1:0.8:0.8.

[0020] According to another exemplary embodiment of the present disclosure, there is provided a negative electrode including the negative electrode active material; and a secondary battery including the negative electrode.

[0021]

Beneficial Effects

[0022] By using the negative electrode active material, when the battery is charged and discharged, the a Si b The C matrix can minimize the formation of irreversible phases, so the initial efficiency of the battery can be improved, and the capacity and life characteristics of the battery can be improved due to the improvement of conductivity, physical strength and chemical stability. a Si b The C matrix contains doped metals, so the conductivity can be further improved, so that the capacity and life characteristics of the battery can be further improved. DETAILED DESCRIPTION

[0023] Hereinafter, the present disclosure will be described in more detail to help understanding of the present disclosure.

[0024] The terms and words used in this specification and claims should not be interpreted as general or dictionary meanings, but should be interpreted as meanings and concepts that satisfy the technical ideas of the present disclosure based on the principle that inventors can appropriately define the concepts of the terms in order to describe their own disclosure in the best manner.

[0025] The terms used in this specification are only used to describe exemplary embodiments rather than to limit the present disclosure. Singular forms are intended to include plural forms unless the context clearly indicates otherwise.

[0026] It should be understood that the terms "includes", "comprising", "having", etc. used in this specification specify the existence of the features, numbers, steps, components or their combinations stated in this specification, but do not exclude the existence or addition of one or more other features, numbers, steps, components or their combinations.

[0027] The negative electrode active material according to the present disclosure comprises M a Si b C-based metal-silicon-carbon particles, wherein the M a Si b M in the C matrix is ​​one or more selected from the group consisting of Li, Mg, Na, Ca and Al, 0.3≤a≤1 and 1≤b≤2. a Si b In the C matrix, Si is silicon and C is carbon.

[0028] The M a Sib The C matrix may have SiC, Si and M a Si b C structure with three phases coexisting.

[0029] In SiO2, which is a silicon-based particle commonly used as a negative electrode active material x (0≤x<2) particles, when driving the battery, the x (0≤x<2) forms an irreversible phase. Therefore, the initial efficiency of the battery is low. In addition, due to the SiO x (0≤x<2) has low physical strength and chemical stability, so the volume of the negative electrode changes excessively during battery charge and discharge, and SiO x (0≤x<2) has low conductivity. Therefore, when using SiO x In the case of a battery with (0≤x<2), there is a problem of reduced capacity and life.

[0030] On the contrary, since the SiC matrix does not contain SiO2, the formation of the irreversible phase can be minimized, so that when using the negative electrode active material containing the SiC matrix, the initial efficiency of the battery can be improved. In addition, the SiC matrix has excellent physical strength and chemical stability, making it more suitable for use with SiO2. x (0≤x<2), the volume expansion of the battery is smaller during charge and discharge.

[0031] In addition, with SiO x (0≤x<2), the M a Si b The C matrix has excellent electrical conductivity, making it possible to a Si b When the negative electrode active material is a C matrix, the capacity and life characteristics of the battery can be improved.

[0032] In the M a Si b C matrix, a corresponds to the M a Si b The "number ratio" of M to C in the C matrix, b corresponds to the number ratio of Si to C. a Si b In the C matrix, a may be 0.3 or more and 1 or less, specifically 0.5 or more and 1 or less, and b may be 1 or more and 2 or less, specifically 1.2 or more and 2 or less.

[0033] In the case where a is lower than the above range, the content of M is low, so that the conductivity may be reduced, and in the case where b is higher than the above range, the content of Si is relatively increased, so that a side reaction with the electrolyte may be generated by Si that does not maintain a bonding relationship with carbon or metal, and the volume of the electrode may be excessively increased due to the above Si during battery charge and discharge. In addition, in the case where a is excessively higher than the above range or b is lower than the above range, the content of Si is too low, so that the capacity of the battery may be excessively reduced, and as the ratio of M in the matrix increases, the amount of metal silicide formed is excessive, resulting in instability of the active material, deterioration of life characteristics, etc. Considering the ranges of a and b, the M of the negative electrode active material according to the present disclosure is preferably 0.0447 W / m. a Si b The C matrix is ​​different from the general SiC (silicon carbide). In the case of SiC, the number ratio of Si to C is 1:1, but in the M a Si b In the C matrix, the number of Si is greater than the number of C, and the conductivity can be improved by M a Si b C phase to improve. Therefore, when using the M a Si b In the case where a C matrix replaces chemically stable SiC, the capacity and life characteristics can be improved.

[0034] The M a Si b M in the C matrix is ​​one or more selected from the group consisting of Li, Mg, Na, Ca and Al, and preferably, M is Mg from the viewpoint of reaction stability and the effect of improving the prevention of a side reaction with the electrolyte.

[0035] The M a Si b The C matrix may contain 10 to 35 wt % of M, 45 to 75 wt % of Si, and 15 to 25 wt % of C, preferably 12 to 25 wt % of M, 52 to 70 wt % of Si, and 15 to 25 wt % of C, more preferably 17 to 20 wt % of M, 60 to 65 wt % of Si, and 17 to 23 wt % of C. Within the above range, the effect of improving the conductivity and life characteristics of the negative electrode active material can be preferably improved, and the capacity of the battery can be improved by Si.

[0036] In the M a Si bIn the C matrix, the weight ratio of Si to M can be from 1.5 to 7, preferably from 2 to 5.5, more preferably from 3 to 4.2. The weight ratio within the above range is preferred because the capacity brought by Si can be excellently exhibited at this time, and the initial efficiency and life characteristics can be improved simultaneously.

[0037] Said M a Si b The C matrix can be in the form of particles.

[0038] In this case, said M a Si b The C matrix can contain Si, SiC and M x Si y C, where M is Li, Mg, Na, Ca or Al, 1 < x ≤ 3, and 0.5 < y ≤ 2. Specifically, 1 < x ≤ 2, and 1 < y ≤ 2.

[0039] The contents of Si, C and M can be confirmed by ICP method.

[0040] The average particle size (D 50 ) of the metal-silicon-carbon particles can be from 1 μm to 10 μm, specifically from 1 μm to 7 μm, more specifically from 1 μm to 6 μm. When the average particle size is within the above range, the diffusion resistance of the electrolyte can be reduced. In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% cumulative volume in the particle size distribution curve of the particles. This average particle size (D 50 ) can be measured, for example, using the laser diffraction method. In the laser diffraction method, the average particle size in the range of about sub-micron to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.

[0041] The negative electrode according to another exemplary embodiment of the present disclosure can contain a negative electrode active material, where the negative electrode active material can be the same as the negative electrode active material according to the exemplary embodiment of the present disclosure above. Specifically, the negative electrode can contain a current collector and a negative electrode active material layer provided on the current collector. The negative electrode active material layer can contain a negative electrode active material. In addition, the negative electrode active material layer can further contain a binder and / or a conductive material.

[0042] There is no particular limitation on the current collector as long as it does not cause chemical changes in the corresponding battery and has conductivity. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, baked carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver, etc., can be used. In detail, a transition metal such as copper or nickel that adsorbs carbon well can be used as the current collector. The thickness of the current collector can be 6 μm to 20 μm, but is not limited thereto.

[0043] The negative electrode active material may be contained in the negative electrode active material layer in an amount of 80 wt % to 99.9 wt %, preferably 93 wt % to 98 wt %. When the content of the negative electrode active material is within the above range, the initial efficiency of the battery may be improved, and the conductivity, physical strength and chemical stability may be improved, thereby preferably improving the capacity and life characteristics of the battery.

[0044] The negative electrode active material may further include a graphite active material in addition to the metal-silicon-carbon particles. The use of the graphite active material together with the metal-silicon-carbon particles may improve the charge and discharge characteristics of the battery.

[0045] The graphite-based active material may be one or more selected from the group consisting of graphite such as artificial graphite or natural graphite, graphitized carbon fibers, and graphitized mesocarbon microbeads.

[0046] In the case where the negative electrode active material further comprises the metal-silicon-carbon particles and the graphite active material, the negative electrode active material may comprise the metal-silicon-carbon particles and the graphite active material in a weight ratio of 1:99 to 30:70, preferably 3:97 to 20:80. Within the above range, the improvement of the conductivity and life characteristics of the metal-silicon-carbon particles and the charge and discharge characteristics of the graphite active material can be simultaneously and excellently exhibited.

[0047] The adhesive may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid and materials in which the hydrogen of the above materials is replaced by Li, Na, Ca, etc., and may include various copolymers thereof.

[0048] The binder may be included in the negative electrode active material layer in an amount of 0.1 wt % to 10 wt %, more preferably 0.5 wt % to 5 wt %.

[0049] There is no particular limitation on the conductive material as long as it does not cause chemical changes in the battery and has conductivity. Examples of the conductive material include graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives; and the like.

[0050] The conductive material may be included in the negative electrode active material layer in an amount of 0.1 wt % to 10 wt %, more preferably 0.5 wt % to 5 wt %.

[0051] A secondary battery according to another exemplary embodiment of the present disclosure may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the same as the above-described negative electrode. Since the negative electrode has been described in detail, its detailed description will be omitted.

[0052] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0053] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as it does not cause chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, roasted carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium or silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and the adhesion of the positive electrode active material can be increased by forming fine concave and convex on the surface of the collector. For example, various forms of positive electrode collectors can be used, including films, sheets, foils, nets, porous structures, foams, non-woven fabrics, etc.

[0054] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1Lithium manganese oxide represented by LiMnO4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide, such as LiV3O8, V2O5 or Cu2V2O7; 1-c2 M c2 A nickel-site type lithium nickel oxide represented by a chemical formula of LiMn 2-c3 M c3 A lithium manganese composite oxide represented by LiMn2O4 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4, in which some of the lithium atoms are replaced by alkaline earth metal ions, but not limited thereto. The positive electrode may be lithium metal.

[0055] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0056] Here, the positive electrode conductive material is used to impart conductivity to the electrode, and is not particularly limited as long as it does not cause chemical changes in the manufactured battery and has electronic conductivity. Specific examples thereof may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber made of copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide, potassium titanate, etc.; conductive metal oxides, such as titanium oxide, etc.; conductive polymers such as polyphenylene derivatives, etc. One of them may be used alone, or a mixture of two or more thereof may be used.

[0057] The positive electrode binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Its specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber and various copolymers thereof. One of them can be used alone, or a mixture of two or more thereof can be used.

[0058] There is no particular restriction on the separator that separates the negative electrode and the positive electrode from each other and provides a movement path for lithium ions, as long as it is used as a separator in a common secondary battery. In particular, it is preferred to use a separator that has low resistance to the movement of electrolyte ions and has excellent "electrolyte wetting ability". Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminate of at least two layers thereof. In addition, a general porous non-woven fabric can be used, for example, a non-woven fabric made of glass fiber with a high melting point, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a coated separator comprising a ceramic component or a polymer material can also be used, and a single layer or multilayer structure can be selectively used.

[0059] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., which may be used when manufacturing a lithium secondary battery, but the electrolyte is not limited thereto.

[0060] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0061] As the nonaqueous organic solvent, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0062] Since ethylene carbonate and propylene carbonate, in particular, as cyclic carbonates, are high-viscosity organic solvents among the carbonate organic solvents, they have high dielectric constants to dissociate lithium salts well, and therefore ethylene carbonate and propylene carbonate can be preferably used. In the case of using a mixture of cyclic carbonates and low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in a suitable ratio, an electrolyte with high conductivity can be prepared, and thus this electrolyte can be more preferably used.

[0063] As the metal salt, a lithium salt can be used, and the lithium salt is a material suitable for dissolving in a non-aqueous electrolyte. As the anion of the lithium salt, for example, one or more selected from the group consisting of the following can be used: F -, Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0064] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, improve the discharge capacity of the battery, etc., the electrolyte may further include one or more additives on the basis of the components constituting the electrolyte mentioned above, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-ethylene glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0065] According to another exemplary embodiment of the present disclosure, a battery module including the secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include the secondary battery having high capacity, high rate performance and cycle characteristics, the battery module and the battery pack can be used as a power source for large and medium-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.

[0066] According to another exemplary embodiment of the present disclosure, a method for preparing a negative electrode active material includes introducing a gasified silicon source, a carbon source, a metal source, and a carrier gas into a reaction furnace, and forming a metal-doped M through heat treatment. a Si b C matrix fluid.

[0067] In the formation of the matrix fluid, the gasified silicon source can be obtained by heat treating the silicon source at high temperature to gasify the silicon source. Here, the silicon source can be at least one selected from the group consisting of pure silicon (Si), silane and trichlorosilane. The carbon source can be gaseous. The carbon source can be at least one selected from the group consisting of methane, ethylene, acetylene and methylene. The metal source can be one or more selected from the group consisting of Li, Mg, Ca, Na and Al. Specifically, the silicon source can be silicon, the carbon source can be methane, and the metal source can be Mg. In this case, high-purity Si, C and Mg can be sent into the reactor.

[0068] The carrier gas may be an inert gas. Specifically, the carrier gas may be at least one selected from the group consisting of Ar, He and Ne, and more specifically, the carrier gas may be argon. The matrix fluid formed by the carrier gas may be discharged from the reaction furnace.

[0069] The flow rate of the gasified silicon source may be 100 sccm to 300 sccm, specifically 100 sccm to 250 sccm, more specifically 150 sccm to 220 sccm. The flow rate of the carbon source may be 30 sccm to 180 sccm, specifically 30 sccm to 120 sccm. The flow rate of the metal source may be 30 sccm to 180 sccm, specifically 30 sccm to 150 sccm, more specifically 80 sccm to 120 sccm. The flow rate of the carrier gas may be 550 sccm to 3,000 sccm, specifically 1,000 sccm to 3,000 sccm.

[0070] The ratio of the flow rate of the gasified silicon source, the flow rate of the carbon source, and the flow rate of the metal source may be 1:0.2:0.2 to 1:0.8:0.8, preferably 1:0.3:0.3 to 1:0.6:0.6, and more preferably 1:0.4:0.4 to 1:0.55:0.55. Since M in which a is 0.3 or more and 1 or less and b is 1 or more and 2 or less can be formed within the above range, a Si b C matrix, thus the conductivity of the negative electrode active material and the capacity of the secondary battery can be improved.

[0071] The heat treatment may be performed at 1,000° C. to 2,500° C., specifically 1,800° C. to 2,300° C., and more specifically 1,900° C. to 2,200° C. Within the above range, the carbon source may be stably decomposed, and thus carbon may be smoothly provided.

[0072] Hereinafter, examples will be provided to help understand the present disclosure. However, it will be apparent to those skilled in the art that the following examples are merely examples of the present disclosure, and that various modifications and changes may be made without departing from the scope and spirit of the present disclosure. In addition, these modifications and changes will fall within the scope of the appended claims.

[0073] Example

[0074] Example 1

[0075] (1) Preparation of silicon-carbon particles

[0076] 1) Formation of matrix fluid

[0077] Pure silicon was used as a silicon source, methane gas was used as a carbon source, Mg metal was used as a metal source, and argon gas was used as a carrier gas. While silicon was gasified and introduced into a tube furnace, the temperature of the furnace was maintained at 2,000°C to perform heat treatment within an interval of 80 cm. Here, the flow rate of the gasified silicon was 200 sccm, the flow rate of the methane gas was 100 sccm, the flow rate of the Mg gas was 100 sccm, and the flow rate of the argon gas was 1500 sccm. In this way, Mg was formed. 0.52 Si 1.51 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0078] (2) Manufacturing of negative electrode

[0079] The prepared metal-silicon-carbon active material particles, graphite, carbon black as a conductive material, carboxymethyl cellulose (CMC) as a binder, and styrene-butadiene rubber (SBR) were mixed in a weight ratio of 4.8:91:1:1.7:1.5 to prepare 5 g of the mixture. A negative electrode slurry was prepared by adding 28.9 grams of distilled water to the mixture. The negative electrode slurry was applied to a copper (Cu) metal film having a thickness of 20 microns as a negative electrode collector and dried. Here, the temperature of the circulating air was 60°C. Subsequently, the resultant was rolled, dried in a vacuum oven at 130°C for 12 hours, and then punched into 1.4875 cm 2 to make the negative electrode.

[0080] (3) Manufacturing of secondary batteries

[0081] The prepared negative electrode was used and cut into 1.7671 cm 2 A circular lithium (Li) metal thin film was used as a positive electrode. A porous polyethylene separator was inserted between the positive electrode and the negative electrode, and an electrolyte was injected, thereby manufacturing a lithium coin half-cell, wherein the electrolyte was obtained by dissolving 0.5 wt% of vinylene carbonate and 1M LiPF6 in a mixed solution in which methyl ethyl carbonate (MEC) and ethylene carbonate (EC) were mixed at a mixing ratio of 7:3.

[0082] Example 2

[0083] The metal-silicon-carbon based active material particles in Example 2 were prepared by the same method as in Example 1, except that the flow rate of the vaporized silicon was adjusted to 200 sccm, the flow rate of the methane gas was adjusted to 100 sccm, the flow rate of the Mg gas was adjusted to 70 sccm, and the flow rate of the argon gas was adjusted to 1500 sccm. In this way, the Mg 0.35 Si 1.53 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0084] Example 3

[0085] The metal-silicon-carbon based active material particles in Example 3 were prepared by the same method as in Example 1, except that the flow rate of the vaporized silicon was adjusted to 145 sccm, the flow rate of the methane gas was adjusted to 100 sccm, the flow rate of the Mg gas was adjusted to 100 sccm, and the flow rate of the argon gas was adjusted to 1500 sccm. 0.54 Si 1.08 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0086] Comparative Example 1

[0087] Silicon-carbon based particles, a negative electrode, and a secondary battery were manufactured by the same method as in Example 1 except that the metal source gas was not introduced.

[0088] Comparative Example 2

[0089] (1) Preparation of silicon-oxygen particles

[0090] The metal-silicon-oxygen based particles in Comparative Example 2 were prepared by the same method as in Example 1 except that SiO 2 was used instead of the methane gas in Example 1.

[0091] Here, the content ratio of metal, silicon and oxygen confirmed by ICP was 15:9:36 based on the total weight of the particles. In addition, the average particle size (D 50 ) is 5μm.

[0092] (2) Manufacturing of negative electrode and secondary battery

[0093] A negative electrode and a secondary battery were manufactured by the same method as in Example 1 except that the prepared silicon-oxygen based particles were used.

[0094] Comparative Example 3

[0095] The metal-silicon-carbon based active material particles in Comparative Example 3 were prepared by the same method as in Example 1, except that the flow rate of the vaporized silicon was adjusted to 40 sccm, the flow rate of the methane gas was adjusted to 200 sccm, the flow rate of the Mg gas was adjusted to 100 sccm, and the flow rate of the argon gas was adjusted to 1500 sccm. 0.22 Si 1.56 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0096] Comparative Example 4

[0097] The metal-silicon-carbon based active material particles in Comparative Example 4 were prepared by the same method as in Example 1, except that the flow rate of vaporized silicon was adjusted to 200 sccm, the flow rate of methane gas was adjusted to 200 sccm, the flow rate of Mg gas was adjusted to 200 sccm, and the flow rate of argon gas was adjusted to 1,500 sccm. 0.52 Si 0.82 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0098] Comparative Example 5

[0099] The metal-silicon-carbon based active material particles in Comparative Example 5 were prepared by the same method as in Example 1, except that the flow rate of the vaporized silicon was adjusted to 300 sccm, the flow rate of the methane gas was adjusted to 100 sccm, the flow rate of the Mg gas was adjusted to 100 sccm, and the flow rate of the argon gas was adjusted to 1500 sccm. 0.53 Si 2.12 Here, the atomic ratio of Mg to Si was measured by ICP. In addition, the average particle size (D 50 ) is 5μm.

[0100] Experimental Example 1 Evaluation of discharge capacity, initial efficiency, capacity retention rate and electrode thickness change rate

[0101] The batteries in Examples 1 to 3 and Comparative Examples 1 to 5 were charged and discharged to evaluate the discharge capacity, initial efficiency, capacity retention rate, and electrode (negative electrode) thickness change rate. The results are described in Table 1 below.

[0102] On the other hand, charge and discharge were performed at 0.1 C in the 1st cycle and the 2nd cycle, and at 0.5 C from the 3rd cycle to the 49th cycle. The 50th cycle was terminated in the charged state (in the state where lithium was located in the negative electrode), and after the battery was disassembled to measure the thickness, the electrode thickness change rate was calculated.

[0103] Charging conditions: CC (constant current) / CV (constant voltage (5 mV / 0.005C current cutoff))

[0104] Discharge conditions: CC (constant current) conditions, 1.5V

[0105] The charge capacity (mAh / g) and initial efficiency (%) were obtained from the results of one charge and discharge. Specifically, the initial efficiency (%) was obtained by the following calculation.

[0106] Initial efficiency (%) = (discharge capacity after 1 discharge / 1 charge capacity) × 100

[0107] The capacity retention rate and electrode thickness change rate were calculated as follows.

[0108] Capacity retention rate (%) = (discharge capacity at the 49th cycle / discharge capacity at the 1st cycle) × 100

[0109] Electrode thickness change rate (%) = (final negative electrode thickness change / initial negative electrode thickness) × 100

[0110] [Table 1]

[0111]

[0112] It can be understood with reference to Table 1 that, in Examples 1 to 3, the discharge capacity, initial efficiency, and capacity retention ratio are simultaneously improved to remarkably excellent levels, and the electrode thickness variation ratio is low.

[0113] However, it can be understood that in Comparative Example 1 in which the metal was not introduced into the matrix, the initial efficiency and the capacity retention ratio were reduced due to the reduction in electrical conductivity, and the electrode thickness variation ratio was high.

[0114] Furthermore, it can be understood that in Comparative Example 2, due to the influence of the SiO2 phase forming an irreversible phase, the initial efficiency and the capacity retention ratio are reduced, and the electrode thickness change ratio is significantly high.

[0115] In addition, it can be confirmed that in Comparative Examples 3 to 5 in which the contents of metal, silicon and carbon contained in the metal-silicon-carbon particles are inappropriate, the initial efficiency and capacity retention rate are low, and the electrode thickness change rate is significantly high. Specifically, in Comparative Example 3, the amount of metal doping is low, so that the initial efficiency is low, and the capacity retention rate is low due to the side reaction with the electrolyte, and in Comparative Example 4, the silicon content is low, so that the capacity of the battery is excessively reduced, and the instability of the active material is caused by the excessively high ratio of M in the matrix, so from the perspective of the capacity retention rate and the electrode thickness change rate, an undesirable effect is obtained. In addition, it can be understood that in Comparative Example 5, the silicon content in the matrix is ​​too high, the initial efficiency is low, and the side reaction of the electrolyte caused by silicon is aggravated, so that the capacity retention rate is low and the electrode thickness change rate is high.

Claims

1. A negative electrode active material comprising M a Si b C-based metal-silicon-carbon particles, wherein the M a Si b M in the C matrix is ​​one or more selected from the group consisting of Mg and Ca, 0.3≤a≤1 and 1≤b≤2, The M a Si b C matrix has SiC, Si and M a Si b C structure with three phases coexisting.

2. The negative electrode active material according to claim 1, wherein the average particle diameter D50 of the metal-silicon-carbon-based particles is 1 μm to 10 μm.

3. The negative electrode active material according to claim 1, wherein The M a Si b The C matrix contains Si, SiC and M x Si y C, M is at least one selected from the group consisting of Mg and Ca, 1 < x ≤ 3 and 0.5 < y ≤ 2.

4. The negative electrode active material according to claim 1, wherein The M a Si b The C matrix contains 10 wt % to 35 wt % M, 45 wt % to 75 wt % Si, and 15 wt % to 25 wt % C.

5. The negative electrode active material according to claim 1, wherein In the M a Si b In the C matrix, the weight ratio of Si to M is 1.5 to 7.

6. A method for preparing the negative electrode active material according to claim 1, the method comprising introducing a vaporized silicon source, a carbon source, a metal source, and a carrier gas into a reaction furnace to form a matrix fluid via heat treatment, wherein in the formation of the matrix fluid, the ratio of the flow rate of the vaporized silicon source, the flow rate of the carbon source, and the flow rate of the metal source is 1:0.2:0.2 to 1:0.8:0.

8.

7. The method according to claim 6, wherein the heat treatment is carried out at 1000 °C to 2500 °C.

8. The method according to claim 6, wherein the carrier gas is at least one selected from the group consisting of Ar, He, and Ne.

9. A negative electrode comprising the negative electrode active material according to claim 1.

10. The negative electrode according to claim 9, further comprising a graphite-based active material.

11. A secondary battery comprising: the negative electrode according to claim 9; a positive electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Negative active material for lithium secondary battery and method of preparing for the same

    KR1020150112746A

  • Method and composition for treating neuronal hyper-excitability

    KR1020180124980A

  • Si alloy-containing negative electrode active material for electrical devices

    CN103222091A

  • Negative electrode for lithium secondary battery and its manufacture

    JP1995302588A

  • Hybrid silicon and carbon clathrates

    US20140374673A1